Analisis Faktor Resiko Kejadian Hipertensi dalam Kehamilan Pada Ibu Hamil Trimester III di Puskesmas Cempaka Kabupaten Oku Timur Tahun 2020 - Diana Rahmawati; Suprida Suprida; Turiyani Turiyani (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Hypertension in pregnancy is hypertension that occurs in maternal pregnancy where the systolic and diastolic blood pressure is ≥140/90 mmHg. In East OKU District, third trimester’s pregnancy women who experienced the incidence of hypertension on 2018 was 18 people (22%), on 2019 increased to 20 people (23%), and on 2020 increased more reaches to 26 people (25%). The purpose of this research is to know the relationships between mother age, gravity, family history of hypertension, and obesity with the incidence of hypertension on pregnancy. The method used in this study was analytic survey with cross sectional approach. The population was 104 third trimester’s pregnant women at Cempaka Health Center, East OKU District. The sample got using simple random sampling technique with the total number of sample was 51. The result of research showed that there was relationship between age and the incidence of hypertension on pregnancy, there was no relationship between gravity and the incidence of hypertension on pregnancy, there was relationship between family history of hypertension and the incidence of hypertension on pregnancy, and there was relationship between obesity and the incidence of hypertension on pregnancy. The conclusion of this research is that there was relationship between age, family history of hypertension, and obesity with the incidence of hypertension on pregnancy, while there was no relationship between gravity and the incidence of hypertension on pregnancy. It is suggested in way to promote and prevent the hypertension on pregnancy, counseling is prioritized, especially for at-risk groups.